Application Of Greedy Algorithm In The Problem Of Optimization Of Multiple Constrain Knapsack Problem On Transportation Of Goods - Gradina Nur Fauziah (Jurnal Syntax Admiration, 2022)
Optimization is a method of solving the problem of maximization or minimization. Optimization is very useful to improve performance and productivity performance. Transportation is one of the areas that are very closely related to optimization. The problem of transporting goods with limited transport capacity and the desire to obtain maximum profits is a classic problem in the world of transportation. This problem is often also analogous to using the Knapsack Problem theory. A greedy algorithm applied to Knapsack Multiple Constraint calculations provides better results than manual calculations.